Cultural Infrastructures in Small and Medium- Sized Cities in Germany. A Location Typology of Cultural Services of General Interest - Mager , Christoph; Wagner, Madeleine (Raumforschung und Raumordnung | Spatial Research and Planning, 2022)
Data on cultural infrastructures in Germany are characterised by great heterogeneity in terms of availability and analytical comparability. This is evident in functional typologisations, which are largely limited to major cities and to a small number of cultural indicators. Furthermore, the ongoing discussions about the provision of services of general interest lack quantifiable and qualifiable substantiation that adequately take into account not only technical facilities but also infrastructures that facilitate everyday social life, including educational and cultural amenities. The aim of this paper is to identify location patterns of cultural infrastructures focusing on small and medium-sized towns, which have been largely neglected analytically.We apply a principal component analysis to comprehensive data on infrastructures of nine cultural sectors in order to identify spatial patterns of agglomeration. The linear dimensionality reduction resulted in three components, “Everyday Culture and High Culture”, “Reading and Art” and “Making Music and Educating Oneself”. The results emphasise the role of small and medium-sized towns in providing differentiated cultural services of general interest and provide systematic links for cultural governance.